Assessment of knowledge, attitude and practices regarding COVID-19 pandemic among general population in a suburban city of Western India: a cross sectional study - Badgujar, Jatin; Kadam, Rahul; Sharma, Gaurav; Shah, Akshay; Relwani, Nisha (International Journal Of Community Medicine And Public Health, 2020)
Background: The aim of the present study was to assess the knowledge, attitude and practices (KAP) regarding COVID-19 pandemic among general population. Methods: A cross sectional study was conducted among general population residing in Navi Mumbai, India, by distributing online based predesigned, prevalidated and semi-structured survey questionnaire through social media from 20 April to 27 April, 2020. The survey instrument consisted of questions based on demographic characteristics followed by knowledge (12 questions), attitude (11 questions) and practices (5 questions). Individuals above 18 years of age, able to understand English language and willing to voluntarily consent were included in the study. Results: A total of 817 participants were included in the study. The mean knowledge score was 10.04±1.52 with an overall accurate response rate of 83.70%. Most of the participants had positive attitude regarding COVID-19 pandemic. A positive correlation was found between level of education with mean knowledge scores as well as positive attitude towards COVID-19 using Kruskal-Wallis H test (non-parametric ANOVA) which was statistically significant (p<0.001). Majority of participants followed infection prevention guidelines including the use of facemask (94.61%), appropriate hand hygiene practices (93.26%), maintaining social distancing (97.42%) and avoiding direct personal contact through hand shake/hugging (97.42%). Conclusions: The study highlights the importance of level of education with correct knowledge, positive attitude and appropriate practices. The information can further assist policy makers to predict success or make necessary modifications with respect to infection mitigation measures based on knowledge, attitude and practices of targeted population.